The big book of gun trivia : everything you want to know, don't want to know, and don't know you need to know : carefully adapted for the meanest understanding /: everything you want to know, don't want to know, and don't know you need to know : carefully adapted for the meanest understanding. ([2013]) - Rottman, Gordon L
No abstract available